Gully Head Retreat in the Sub‐Humid Ethiopian Highlands: The Ene‐Chilala Catchment. (3rd May 2017) - Addisie, Meseret B.; Ayele, Getaneh K.; Gessess, Azalu A.; Tilahun, Seifu A.; Zegeye, Assefa D.; Moges, Mikael M.; Schmitter, Petra; Langendoen, Eddy J.; Steenhuis, Tammo S.
Abstract: In the northern highlands of Ethiopia, gully erosion is severe. Despite many efforts to implement gully prevention measures, controlling gully erosion remains a challenge. The objective is to better understand the regional gully erosion processes and to prevent gully head retreat. The study was conducted in the Ene‐Chilala catchment in the sub‐humid headwaters of the Birr River located southwest of Bahir Dar, Ethiopia. Twelve gully heads were monitored during the 2014 and 2015 rainy monsoon phase. We measured gully head morphology and retreat length, soil shear strength, ground water table levels, and catchment physical characteristics. Two active gully head cuts were treated in 2014 and an additional three head cuts in 2015 by regrading their slope to 45° and covering them with stone riprap. These treatments halted the gully head advance. The untreated gullies were actively eroding due to groundwater at shallow depths. The largest head retreat was 22.5 m, of which about half occurred in August of the first year when the surrounding soil was fully saturated. Lowering both the water table and protecting the gully heads can play a key role in reducing gully expansion and soil loss due to gully erosion in the Ethiopian highlands. Copyright © 2016 John Wiley & Sons, Ltd.